Representation of Serbia in foreign press online - Milošević, Ivana D. (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2015)
This paper presents the results of the treatment of Serbia on German, American, British and French websites during the period of January to March 2013. A quarterly quantitative and qualitative content analysis showed that 12 internet websites have had 644 news items about the situation in Serbia. Apart from the number of news items, the tone of the reports was also examined and it was found to be overwhelmingly neutral. The results obtained demonstrate that sports manifestations were most often covered events, thus making Novak Đoković the most frequently mentioned Serbian person on the select websites. It has been over 100 years since the first research pertaining to Serbia’s treatment in the foreign media. The starting hypothesis that reporting on Serbia has changed was partially confirmed. One might come under the impression that even though war years and sanctions are behind Serbia, journalists still mention Yugoslavia, Slobodan Milošević, Ratko Mladić, wars and poverty every time this is in their favour. Usage of verbal stereotypes has been noticed, while Serbs have been represented as warlike people, nationalists, sometimes with the addition of “extreme”. The image of Serbia is different that it had been 100 years ago, but not enough to prove the starting hypothesis.
Keywords: Serbia; media representations; stereotypes; PREJUDICE; INTERNET; media